A dinâmica da gestão de pessoas em uma unidade de internação pediátrica - Tereza Cristina Peixoto (2011)
People management nowadays is considered strategic in the innovation of management models focused on the efficiency of services and competitiveness of the organizations. The goal of this study is to analyze the vision of health professionals regarding people management practices in a pediatric unit considering formal elements that characterize the work. To do so, qualitative approach was used, once the study object involves the understanding of dynamic and subjective aspects, as well as the description of the reality. The study was settled at a pediatric unit at a hospital that adopts the participative management model. The subjects of the study was the management of the unit, composed of the manager and three coordinators of the Functional Unit (medical coordinator, nursing coordinator, and administrative coordinator) and a heterogeneous group formed by 16 health professionals of the following fields: Psychology, Social Service, Occupational Therapy, Nursing, Medicine, Physiotherapy, Nutrition, and Hearing and Speech Therapy, and an assistant professional, coming to a total of 21 people. Data collection happened two ways: first, secondary data analysis using the documents related to people management presented by human recourses and, for primary data analysis; interviews with semi-structured script were done. Data analysis was based on Bardin (2009). In this analysis, four categories were created: Work at a University hospital privileged locus; Shared management advances and retreats; Care of gravely ill children uniqueness of pediatric work; and finally Image (action) of people management practices. As final consideration, it is concluded that, in the perspective of the employees, there is a distance between the prescribed and the reality regarding people management. There is a lack of actual participation of the employees in people management practices. This is due to the existence of many professional links besides the ones of the University, such as temporary contracts and contracts with the institution, with salary and work laws discrepancies. Besides the lack of management practices that consider the complexity involved with the work object in the pediatric unit, especially concerning the mental health of employees and need of strategies to promote consolidation of an organizational culture that is democratic and integrated. Professional corporatism is other factor that makes the work processes, employees union and daily communication more difficult.